The Senkaku Islands Confrontation and the Transformation of Japan’s Defense - Midford, Paul. author. aut Link
XIV, 160 p. 7 illus., 6 illus. in color.
Keywords: “This book presents the most recent and compelling assessment of Japan’s drastic security policy shift since December 2022. Informed by defensive realism, it convincingly argues that the shift was meant for homeland territorial defense against Chinese threats, rather than for global operations. Highly recommended.” --Tsuyoshi Kawasaki, Professor of International Politics, Simon Frazer University, Canada. "Midford builds a strong case that Japan's increasing defense spending and capabilities are not primarily to return as a regional military power but rather are narrowly focused on Japan's own territorial defense, which has important implications for the future regional balance of power." --Andrew L. Oros, Professor of International Studies, Washington College, USA. “Empirically rich and convincingly argued.” --Tom Phuong Le, Chair of Politics, Pomona College, USA. This book argues that the transformation of Japan’s defense since 2012 has been triggered by the emergence of the first threat to Japan’s territorial integrity since 1945, namely China’s continual challenging of Japan’s control of the Senkaku Islands. It shows how this threat led to Japan building its own version of an A2/ AD strategy and contributed to the demise of the prohibition on not procuring long-range missiles. It posits that the new security documents of 2022 that mandate increasing defense spending to 2% of GDP, is the culmination of this Senkaku-driven post-2012 defense transformation. Nonetheless, Japan’s defense transformation faces significant challenges, including geographic and demographic, base-community relations, and limited SDF capacity. The author analyzes the implications of Japan’s defense transformation for its involvement in a military conflict over Taiwan between China and the USA. Dr. Paul Midford is Professor of International Relations at Meiji Gakuin University in Yokohama Japan. He specializes in Japanese foreign and security policies, East Asian international relations and security, and renewable energy.